Synthesis of Azidohydrin from Hura crepitans Seed Oil: A Renewable Resource for Oleochemical Industry and Sustainable Development. (21st November 2012) - Adewuyi, Adewale; Göpfert, Andrea; Wolff, Thomas; Rao, B. V. S. K.; Prasad, R. B. N.
Abstract : The replacement of petrochemicals by oleochemical feedstocks in many industrial and domestic applications has resulted in an increase in demand for biobased products and as such recognizing and increasing the benefits of using renewable materials. In line with this, the oil extracted from the seed of Hura crepitans was characterized by an iodine value of 120.10 ± 0.70  g Iodine/100 g and a saponification number of 210.10 ± 0.40  mg KOH/g with the dominant fatty acid being C18:2 (52.8 ± 0.10 %). The epoxidised fatty acid methyl esters prepared from the oil were used to synthesise the azidohydrin with a yield of 91.20%. The progress of the reaction was monitored and confirmed using FTIR and NMR. This showed the seed oil of Hura crepitans as a renewable resource that can be used to make valuable industrial and domestic products.